Dampak Pertanian Organik dan Konvenional pada Biodiversitas dan Sifat Kimia Tanah pada Budi Daya Tanaman Padi Sawah - Lilik Tri Indriyati; Sugeng Santoso; Enjeline Irianti (Jurnal Ilmu Pertanian Indonesia, 2024)
The phenomenon of leveling off and environmental degradation that occurs as a negative impact of the excessive use of chemical fertilizers and pesticides encourages the development of organic farming systems that can produce crop yields that are not contaminated and free from synthetic chemicals and maintain a healthier environment. The research was conducted from October to December 2022 by taking soil samples from farmers' paddy fields in Tegal Regency using an organic (Cawitali Village) and conventional or non-organic (Jembayat Village) farming system. Composite soil samples were taken from a soil depth of 0 to 20 cm from the soil surface using a soil drill on lowland rice fields with organic farming systems and conventional farming after harvest. The analysis of the chemical properties of the soil carried out was C-organic (Walkley and Black), N-total (Kjeldahl), CEC and soil bases (exch-Ca, exch-Mg, exch-K, and exch-Na), total P (25% HCl) and available P (Bray I), while the observed soil biological properties were the total number of microbial and fungal populations. The results showed that organic paddy soil's chemical and biological properties were relatively higher than conventional paddy soil's. Total fungi in organic lowland soils were lower than in conventional paddy fields. The nutrient status of C-organic and N-total in organic rice fields tended to increase compared to conventional rice fields, namely from very low to low and low to moderate, respectively. In contrast, the other nutrient statuses observed tended to remain relatively unchanged. Generally, soil biological and chemical properties were better in organic farming than in conventional farming systems. Keywords: leveling off, organic farming, conventional farming, nutrient status